The Diachronic Evolution of the Distribution of Chinese and Western Cultural Content in High School English Textbooks: Based on the "Reading" Section of the Compulsory Textbooks of the People's Education Press Edition - Zhu, Yan (Education Insights, 2025)
With the deepening of globalization and the increasing emphasis on national cultural identity in educational discourse, the arrangement of cultural content in English textbooks has received increasing attention. This paper takes the People's Education Press (PEP) high school English compulsory textbooks as the research object, and uses the "Framework for Analyzing Cultural Representations in Foreign Language Textbooks" to conduct a diachronic comparative analysis of the Chinese and Western cultural content in the "Reading" sections of the 2004 and 2019 editions. The study finds that in the new edition, the proportion of learners' native culture has significantly increased, while the proportion of target language country culture has decreased. The proportion of Chinese and Western cultural comparison content has also noticeably increased. In terms of thematic context, both editions prioritize the "Human and Society" theme. The findings of this study provide theoretical support and practical insights for English textbook compilation and teaching practice.